Community Education A Profile of Two Communities. A Community Education Study Guide. (Distributed by ERIC Clearinghouse, 1981)
This booklet is designed to be used as a workbook to present the concept of community education in a format which addresses important questions any community needs to consider as it explores community education. The booklet can be used in conjunction with the videotape "Community Education: A Profile of Two Communities." However, the contents of the booklet are self-explanatory and can be used independently. The booklet begins with a profile and a discussion of the philosophy of two model community education programs. The next section of the booklet, which comprises its bulk, is a study guide which can be used individually or with groups for exploring community education. Five components of a community education program are examined: extended use of public school facilities, citizen involvement, interagency cooperation, needs assessment of communities, and leadership. The format for each component is broken into three sections: a brief overview of how the two model communities have developed each part of their community education program; a series of facts and issues to broaden the reader's perspective of the implications this component has for community education development; and several key questions which communities and schools need to consider in beginning to implement community education. The last section of the booklet lists a variety of community education resources available to communities and schools. (Author/RM)